The evolution and persistence of polyploidy in Oxalis obliquifolia Steud. ex A.Rich. populations in Gauteng - Oberlander, Kenneth Carl (University of Pretoria, 2023)
Dissertation (MSc (Plant Science))--University of Pretoria, 2022.